2009
DOI: 10.1158/0008-5472.can-09-0371
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HuR in Gemcitabine Efficacy in Pancreatic Cancer: HuR Up-regulates the Expression of the Gemcitabine Metabolizing Enzyme Deoxycytidine Kinase

Abstract: RNA-binding protein

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
238
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 158 publications
(253 citation statements)
references
References 16 publications
13
238
2
Order By: Relevance
“…Increased expression levels of HuR may increase the cytotoxicity of GEM and reduce chemoresistance to this drug in a variety of malignant cell types. A previous in vitro study demonstrated that the modulation of dCK expression via HuR overexpression markedly sensitized pancreatic cancer cells to GEM (11). Similar results were identified in human gallbladder cancer cells (14), and an in vivo study has also demonstrated that the status of HuR expression in various cancer cells is closely associated with response to GEM and GEM-based chemotherapy in patients with pancreatic cancer (11,15).…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…Increased expression levels of HuR may increase the cytotoxicity of GEM and reduce chemoresistance to this drug in a variety of malignant cell types. A previous in vitro study demonstrated that the modulation of dCK expression via HuR overexpression markedly sensitized pancreatic cancer cells to GEM (11). Similar results were identified in human gallbladder cancer cells (14), and an in vivo study has also demonstrated that the status of HuR expression in various cancer cells is closely associated with response to GEM and GEM-based chemotherapy in patients with pancreatic cancer (11,15).…”
Section: Introductionsupporting
confidence: 63%
“…numerous types of malignancy have been investigated in vivo and in vitro (5)(6)(7)(8)(9)(10)28). To the best of our knowledge, the first study that identified upregulated HuR expression as a significant marker for an improved response to GEM-based chemotherapy in patients with pancreatic cancer was published in 2009 (11). The study also observed that high HuR expression levels predicted a favorable prognosis in these patients (11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations